Rationality Concepts in Environmental Valuation - Frör, Oliver (Hohenheimer volkswirtschaftliche Schriften, 2018)
Survey based valuation techniques like the Contingent Valuation Method (CVM) rely particularly on the premise of respondents' rationality when answering willingness to pay (WTP) questions. Results of CVM surveys have repeatedly put this fundamental assumption into question. This study adopts a more realistic view of rationality accounting for respondents' limited capacities to process information. Based on cognitive psychology a technique to detect and analyze the bounds of rationality inherent in WTP statements is developed. Using an empirical example, the influence of bounded rationality on the validity of CVM results is analyzed. It is shown that individual differences in information processing play a major role. From these results recommendations for future survey design are developed.